Olena Svitlychna. Ukrainian ethnic style in the interpretation of the younger generation (on the examples of works by students-designers of Borys Grinchenko Kyiv University) : Olena Svitlychna. Ukrainian ethnic style in the interpretation of the younger generation (on the examples of works by students-designers of Borys Grinchenko Kyiv University) - Svitlychna , Olena (Young Scholars Grinchenko – Seton International Journal, 2022)
Olena Svitlychna. Ukrainian ethnic style in the interpretation of the younger generation (on the examples of works by students-designers of Borys Grinchenko Kyiv University)